The Construction of Cooperation Contract in Sharia Banking with Qowaid Fiqhiyyah Muamalah Review - Naisabur, Nanang; Nova, Nova (STAI AL-FALAH CICALENGKA, 2022)
The development of Islamic banking at this time is progressing. The public is interested in the profit-sharing system offered by Islamic banking. There are characteristics of Islamic banking that distinguish it from conventional banking in general, namely the existence of sharia contracts which are the basis for the establishment of economic activities. Here the author examines more deeply about the construction of Islamic banking contracts using the literature analysis method, which is reviewed from several sources of books and journals which are then researched and associated with the issues discussed. The results of the study stated that there are several factors that influence the obstacles in the construction of cooperation contracts in Islamic banking. Among these factors is the tendency of Islamic financial institutions or Islamic banking to implement sharia cooperation contracts on certain products only with reference to conventional interest. This is nothing but based on two mutually attractive laws, namely between sharia law and conventional law. In addition, the lack of qualified human resources in the field of Islamic banking is also a factor, especially in understanding the rules of fiqhiyyah. This Fiqhiyyah rule has a close relationship, especially in running the Islamic economy. Then can this sharia principle or contract be maintained and developed in this sharia banking product by referring to fiqhiyyah rules or does it continue to refer to existing conventional law? Keywords: Sharia Banking, Cooperation Agreement, Fiqhiyyah Rules AbstrakPerkembangan perbankan syari’ah pada masa ini tengah mengalami kemajuan. Masyarakat tertarik pada sistem bagi hasil yang ditawarkan oleh perbankan yari’ah. Terdapat karakteristik perbankan syari’ah yang menjadi pembeda dari perbankan konvensional pada umumnya, yakni adanya akad-akad syari’ah yang menjadi landasan dalam terjalinnya kegiatan ekonomi. Disini penulis meneliti lebih dalam mengenai konstruksi akad perbankan syariah dengan menggunakan metode analisis pustaka yakni dikaji dari beberapa sumber buku dan jurnal yangkemudian diteliti dan dikaitkan dengan isu yang dibahas. Hasil penelitian tersebut menyatakan bahwa ada beberapa faktor yang mempengaruhi hambatan dalam perkembangan produk perbankan syari’ah ini. Diantara faktor tersebut ialah adanya kecenderungan Lembaga keuangan syari’ah atau perbankan syari’ah dalam mengimplementasikan akad-akad syari’ah dalam produknya hanya pada akad-akad tertentu sehingga akad-akad lain belum mendapatkan tempatnya dalam Lembaga keuangan syari’ah atau perbankan syari’ah ini. Hal tersebut tidaklain didasarkan dari dua hukum yang saling tarik menarik yakni antara hukum syari’ah dengan hukum konvensional. Selain itu kurangnya sumber daya manusia yang mumpuni dalam bidang perbankan syari’ah juga menjadi salah satu faktor terutama dalam pemahaman kaidah fiqhiyyah. Kaidah Fiqhiyyah ini memiliki kaitan erat khususnya dalam menjalankan perekonomian Islam. Kemudian apakah prinsip atau akad syari’ah ini dapat dipertahankan dan dikembangkan dalam produk perbankan syari’ah ini dengan merujuk pada kaidah fiqhiyyah atau justru terus merujuk pada hukum konvensional yang ada? Kata Kunci : Perbankan Syari’ah, Akad Kerjasama, Kaidah Fiqhiyyah